Meta-Analysis of the Effect of the Application of the Problem-Based Learning Model on the Mathematical Problemsolving Ability of Students in Mathematics Learning - Chintya Novelia; Ali Asmar; Edwin Musdi; Armiati Armiati (CV. Green Publisher Indonesia, 2023)
Students' problemsolving abilities can be improved in one way, namely by choosing the right mathematics learning model. One learning model that can be used is the problembased learning model. The aim of this research is to re-analyze the influence of the problembased learning model on students' mathematical problemsolving abilities by reviewing, summarizing data and analyzing several research results that have been published on Google Scholar as many as 14 articles using statistical methods. The type of research in this article is meta-analysis research. The research steps include data collection, coding, calculating the increase in problem solving abilities and effect size, and drawing conclusions. Based on the research results, the average effect size is 2.02 in the very large category. Based on the average effect size, it can be concluded that the problembased learning model influences students' mathematical problemsolving abilities.